2019
DOI: 10.1177/2167479519837549
|View full text |Cite
|
Sign up to set email alerts
|

(Re-)presenting the Paralympics: Affective Nationalism and the “Able-Disabled”

Abstract: The relationship between media, sport, nations and nationalism is well established, yet, there is an absence of these discussions at the intersection of communication, Paralympics and disability studies. This omission is particularly significant considering the rapid commodification of the Paralympic spectacle, exacerbated by the entry of Channel 4 (C4) as the UK Paralympic rights holders, that has seen the games become an important site of disability (re-)presentation. In this article, we focus on the constru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(51 citation statements)
references
References 37 publications
(66 reference statements)
4
47
0
Order By: Relevance
“…Indeed, this nuance in the data present a clear ‘disruption’ in disability discourse structured through the advancement and cultural celebration of technologically enhanced disabled bodies that has led to greater palatability of this form of disabled body. At the same time, we identify a discomfort with other, more severe and ‘hidden’ disabilities, demonstrating how the inclusion and hyper-visibility of some select forms of disability are structured by the exclusion and hypo-visibility of others (Pullen et al, 2019). This audience data therefore connects to the long-standing concern that both Paralympic broadcasters, marketers and Games organisers celebrate some disabled bodies more than others (Beacom et al, 2016; Bruce, 2014; Howe, 2008).…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…Indeed, this nuance in the data present a clear ‘disruption’ in disability discourse structured through the advancement and cultural celebration of technologically enhanced disabled bodies that has led to greater palatability of this form of disabled body. At the same time, we identify a discomfort with other, more severe and ‘hidden’ disabilities, demonstrating how the inclusion and hyper-visibility of some select forms of disability are structured by the exclusion and hypo-visibility of others (Pullen et al, 2019). This audience data therefore connects to the long-standing concern that both Paralympic broadcasters, marketers and Games organisers celebrate some disabled bodies more than others (Beacom et al, 2016; Bruce, 2014; Howe, 2008).…”
Section: Resultsmentioning
confidence: 81%
“…As many participants saw it, the significant increase in C4’s live Paralympic coverage moved the games from ‘ the background’ , giving it parity with non-disabled events such as the Olympic Games. As we have identified in previous work, C4 had a strategy of focusing on the most successful, medal-winning athletes (See Pullen et al, 2019) in an attempt to capture the national audience interest. The use of this strategy clearly resonated with audiences, with many claiming their reason for watching the Paralympics was to experience another sporting event that delivered national medal success:I look at them the same.…”
Section: Resultsmentioning
confidence: 99%
“…The IGs offers rich symbolism of the patriotic body and its relationship to the imagined nation. As Pullen et al (2020) insightfully observed in relation to the Paralympic Games, the production of "hypervisible" and "marginalized" Meanwhile those who remain broken, jobless, homeless, and/or with major mental health problems remain partially or "in-"visible. (6)…”
Section: The Invictus Gamesmentioning
confidence: 99%
“…Described as a 'prosthetic aesthetic', the emergence of this disability/celebrity culture has been viewed as a new sensibility toward the disabled prosthesis body (Tamari 2017). Here the Paralympics -a powerful cultural agent and mediator in constructing and transmitting highly affective images and vicarious experiences disability (Elliot 2003) -captures this cultural moment in the hyper-visible display of technologically enhanced para-sport bodies (Pullen et al 2019). Termed 'cyborg', 'posthuman' and 'technotopic', this form of disabled body has received much critical attention (see Balsamo 1996, Kirkup et al 2000, Cherney 2001, Siebers 2008, Howe 2008, Haraway, 1991.…”
Section: Disability Gender and The Paralympic Gamesmentioning
confidence: 99%
“…For us, the hyper-visibility of disability provides for an important intervention into how specific forms of disability come into being and articulate with specific cultures, institutions and practices (Diedrich 2005). Indeed, whilst there has been attention on the increasing prominence of the technologically enhanced disabled body (see Howe 2011, Howe andSilva 2017) and an ablenational framing (see Pullen et al 2019) there has been sparse scholarly consideration (save for a mere handful of studies, for instance, Schell and Rodriguez 2001, Buysse and Borcherding 2010) on the complex relationships between technology, disability and gender.…”
Section: Introductionmentioning
confidence: 99%